Modeling gas breakthrough and flow phenomena through engineered barrier systems using a discrete fracture approach - Fabbri, Heber; Sánchez, Marcelo; Maedo, Michael; Cleto, Pedro [UNESP]; Manzoli, Osvaldo [UNESP] (Elsevier, 2023)
Compacted clays are being considered to build engineered barrier systems (EBS) intended for the safe isolation of high-level nuclear waste (HLW) and spent nuclear fuel (SNF). The corrosion of the metallic canister containing the HLW/SNF will lead to the generation and buildup of the gas pressure in the more internal part of the clay buffer. This phenomenon would eventually trigger the formation and propagation of fractures in the clay barrier, jeopardizing its safety functions. In this work we propose to use the fragmentation technique (MFT) to model evolving fractures in clays triggered by gas pressurization. The MFT has been successfully used to model the formation of fractures in concrete, drying cracks in soil, hydraulic and thermo-fractures in rocks. In this work, we extend the MFT to deal with multiphase fluid flow in deformable porous media, and we upgraded a fully coupled computer finite element code using the extended technique. The proposed approach is first verified against analytical solutions and is then applied to model gas breakthrough experiments in clays. A very satisfactory performance of the method is observed in all the analyses, showing the potential of the MFT to tackle multiphase flow problems in deformable porous media with evolving discontinuities.
Keywords: Breakthrough gas pressure coupled hydro-mechanical modeling; Discrete fracture model; Gas migration in compacted clay barriers; Mesh fragmentation technique